A 23-year bibliometric analysis of the development of global research on hereditary renal carcinoma - Lan, Xiaopeng; Feng, Mei; Lv, Ji; Zhang, Luchen; Hu, Pengcheng; Wang, Yizhen; Zhang, Yanhui; Wang, Shen; Liu, Chunzhao; Liu, Chunlei (Frontiers in Oncology, 2024)
Objectives: Medical research continues to be extensively devoted to investigating the pathogenesis and treatment approaches of hereditary renal cancer. By aspect including researchers, institutions, countries, journals, and keywords, we conduct a bibliometric analysis of the literature pertaining to hereditary renal cancer over the last 23 years. Methods: From the Web of Science Core Collection, we conducted a search for publications published between January 1, 2000 and November 28, 2023. Reviews and original articles were included. Results: A cumulative count of 2,194 publications met the specified criteria for inclusion. The studies of the included articles involved a collective of 2,402 institutions representing 80 countries. Notably, the United States exhibited the highest number of published documents, constituting approximately 45.49% of the total. The preeminent institution in this discipline is the National Cancer Institute (NCI), which maintains a publication volume of 8.98%. In addition to being the most prolific author (125 publications), Linehan WM's works received the highest number of citations (11,985). In a comprehensive count, 803 journals have published related articles. In the top 10 most recent occurrences were the terms "hereditary leiomyomatosis" and "fumarate hydratase." Conclusion: This is the first bibliometric analysis of the literature on hereditary renal cancer. This article offers a thorough examination of the present status of investigations concerning hereditary renal cancer during the previous 23 years.